1998
DOI: 10.1074/jbc.273.21.12753
|View full text |Cite
|
Sign up to set email alerts
|

Energy Thresholds in Brain Mitochondria

Abstract: Decreases in mitochondrial respiratory chain complex activities have been implicated in neurodegenerative disorders such as Parkinson's disease, Huntington's disease, and Alzheimer's disease. However, the extent to which these decreases cause a disturbance in oxidative phosphorylation and energy homeostasis in the brain is not known. We therefore examined the relative contribution of individual mitochondrial respiratory chain complexes to the control of NAD-linked substrate oxidative phosphorylation in synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
95
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(108 citation statements)
references
References 55 publications
12
95
1
Order By: Relevance
“…However, variations in the complex I threshold in different brain mitochondria have already been demonstrated. It was found that synaptic rat brain mitochondria have complex I threshold of ϳ25% (48). Also in PC12 cells the threshold for complex I was ϳ7% (28), which is similar to what we observed in the striatal cells (Table II).…”
Section: Fig 4-continuedsupporting
confidence: 88%
“…However, variations in the complex I threshold in different brain mitochondria have already been demonstrated. It was found that synaptic rat brain mitochondria have complex I threshold of ϳ25% (48). Also in PC12 cells the threshold for complex I was ϳ7% (28), which is similar to what we observed in the striatal cells (Table II).…”
Section: Fig 4-continuedsupporting
confidence: 88%
“…Dox-induced cells displayed a significant decrease in both activity of complex I as well as complex I substrate-mediated oxygen consumption compared with untreated controls. A previous report (61) suggested that a reduction of complex I activity by as little as 25% in isolated brain synaptosomes was sufficient to render a significant effect on complex I substrate-mediated respiration. We found that elevation of MAO-B levels by 2-3-fold in differentiated dopaminergic PC12 resulted in a 40% inhibition of complex I activity, akin to what is observed in PD patients (62)(63)(64), and a corresponding decrease in oxygen consumption rates.…”
Section: Discussionmentioning
confidence: 92%
“…The danger in these conditions is that the multi-factorial nature of the coupling between the oxidative cycles of the respiratory chain and the adenosine disphosphate phosphorylation may lead to significant miscalculations. Thus, Davey et al showed that in rat brain synaptosomes, differential levels of inhibition of the complexes I, III and IV were required to induce significant decreases of ATP levels: while only 20% inhibition of the complex I was sufficient for the inhibition of ATP production, the complex III was much more resilient, and required a drastic inhibition of up to 80% to achieve the same block of ATP production (Davey et al 1998). It is also Figure 1.…”
Section: Functional Consequencesmentioning
confidence: 99%